Halal logistics opportunities and challenges - Zailani, S.; Iranmanesh, M.; Aziz, A.A.; Kanapathy, K. (Emerald, 2017)
Purpose: The purpose of the paper is to investigate the challenges and opportunities for logistics companies in Malaysia to adopt halal logistics. Logistics plays a key role in protecting the halal integrity of halal food through proper transportation, storage and handling along the supply chain until it reaches its final destination. Design/methodology/approach: This research builds on existing research published in the Journal of Islamic Marketing on halal logistics. In addition to an extensive literature review, five focus group discussions were conducted to discover the challenges and opportunities with regards to halal logistics services in Malaysia. Findings: The results show that the future market demands and the competitive opportunities related to halal services are the main motivators of first movers in halal logistics. The early adopters of halal logistics face several challenges such as ambiguous halal guidelines, lack of international halal certification, lack of collaboration among governing agencies (i.e. logistics service providers (LSPs), Jabatan Kemajuan Islam Malaysia (JAKIM) and Halal Industry Development Corporation), a lack of cost-effective standards, an overly competitive transportation sector, lack of demand, lack of halal logistics compulsion, financial challenges and a general misunderstanding of halal practices. Practical implications: The findings of the present study may help government policy makers recognise the issues that should be addressed in motivating logistics companies to adopt halal practices. Originality/value: Although halal logistics plays a key role in protecting the halal integrity of halal products, there are few halal LSPs. This study contributes to the advancement of knowledge on the challenges and opportunities of adopting halal logistics.